Safe and sound : a novel - McHugh, Laura (Random House, 2024)
"Amelia and Kylee, two young sisters, were found unharmed in their upstairs bedroom the night their teenage cousin Grace, who was babysitting them, vanished from the farmhouse in rural Missouri, leaving behind evidence of a violent struggle. Grace had been on the verge of escaping their dead-end town, the first in their family to go to college instead of getting married and going to work at the meatpacking plant. Her disappearance is a warning to any local girl who dared hope for better. Now about to graduate high school, Amelia and Kylee dream about getting out of their small town of Beaumont one day, but the likelihood of that happening seems as low as that of Grace being found. When a discovery of human remains reveals a disturbing connection to Grace, the sisters think they finally know who took her, but as they dig deeper into Grace's past, they unearth long-buried secrets and a growing list of suspects. In a town no one ever leaves, there are only so many places to hide, and the sisters vow to find Grace, dead or alive. As they draw closer to the truth and slip deeper into danger, they question how far someone would go to put a woman in her place, or to cover up a crime. The answer is worse than they could have imagined, and in the end, it won't just be Grace they're trying to save--they'll have to fight for their lives"--